Comparative Study of Structural and Quality Controls for Grouted Sleeve Connections in Different Standards: Connection Technology, Design, and Mechanical Requirements - Shuoting Xiao; Nikita Igorevich Fomin; Jiaxin Li; Jinhong Gu (Buildings)
As one type of critical load-bearing element in precast concrete structures, grouted sleeve (GS) connections enable efficient force transmission between reinforcing bars while maintaining structural integrity. Despite their growing global adoption, significant variations exist in design philosophies, construction specifications, and performance requirements among regional standards. Through bibliometric analysis, the most active countries and regions in GS application and research worldwide were identified, and the relevant technical standards established by these countries and regions were systematically reviewed. By comparing standards from Asia, the Americas, Europe, and Oceania, the main differences in design philosophy, construction quality control, material specifications, and performance requirements among these standards were analyzed and identified. The results show that different standards have a conceptual difference at the materials and quality control level, with one approach focusing on stricter management of sleeve materials and more detailed on-site construction requirements, and another approach emphasizing testing-based methods and third-party verification. These standards can be divided into the following two categories for the design limits of GS tensile performance: one category takes multiples of the yield strength of the connected reinforcing bars as the limit, and the other category takes multiples of the tensile strength of the connected reinforcing bars as the limit. Regarding mechanical performance requirements, standards using the ultimate tensile strength of the connected reinforcing bars as the control parameter differ from those using multiples of yield strength in their performance requirements for connections of low-strength and high-strength reinforcing bars. The variation in yield-to-tensile strength ratios among steel grades across different countries is a key factor leading to these different requirements. When using the uniform steel bar material properties specified in the standard for quantification, as the bar strength increases from approximately 240 MPa to 600 MPa, the minimum required ratio of the limits for standards based on multiples of yield strength and multiples of tensile strength increases from 0.79 to 1.07. When applying GS connections to reinforcing bars of varying strength levels, using fixed strength multiplier requirements may result in uneconomical designs or create technical challenges in achieving the required strength.